Phenotypic and Genotypic Characterization of Novel Polyvalent Bacteriophages With Potent In Vitro Activity Against an International Collection of Genetically Diverse Staphylococcus aureus - Whittard, Elliot; Redfern, James; Xia, Guoqing; Millard, Andrew; Ragupathy, Roobinidevi; Malic, Sladjana; Enright, Mark C. (Frontiers in Cellular and Infection Microbiology, 2021)
Phage therapy recently passed a key milestone with the recent success of the first regulated clinical trial using systemic administration. In this case to treat invasive Staphylococcus aureus infections. Here we examined some of the features of a collection of 78 lytic S. aureus phages propagated using a modified S. carnosus host, as well as a clinical S. aureus isolate. S. carnosus hosts eliminate the threat of contamination with staphylococcal prophage - the main vector of horizontal gene transfer of bacterial virulence in S. aureus. We determined the host range of these phages against an international collection of 185 clinical S. aureus isolates with 56 different multilocus sequence types that includes multiple representatives of all epidemic MRSA and MSSA clonal complexes. We found that 40 of our 78 phages were able to infect > 90% of study isolates, 15 were able to infect > 95% with two that could infect all 184 clinical isolates but not a phage-resistant mutant generated in previous work. We selected the 10 phages with the widest host range for in vitro characterisation by planktonic culture time / kill analysis against four isolates:- modified S. carnosus TM300H, methicillin-sensitive isolates D329 and 15981 and MRSA isolate 252. Six out of these ten isolates were able to rapidly kill, reducing cell numbers of at least three isolates. The four best-performing phages, in this assay, were further shown to be highly effective in reducing 48h biofilms on polystyrene formed by eight ST22 and eight ST36 MRSA isolates. Genomes of 22 of the widest host-range phages showed they elonged to the Twortvirinae subfamily of the order Caudovirales in three main groups corresponding to Silviavirus, and two distinct groups of Kayvirus. These genomes assembled as single linear dsDNAs with an average length of 140 kb and a GC content of c.30%. Phages that could infect > 96% of S. aureus isolates were found in all three groups and these have great potential as therapeutic candidates if, in future studies, they can be formulated to maximise their efficacy and eliminate emergence of phage resistance by using appropriate phage combinations.